2014
DOI: 10.1519/jsc.0000000000000522
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Responses to Two High-Intensity Intermittent Exercise Protocols

Abstract: The purpose of this study was to compare peak cardiorespiratory, metabolic, and perceptual responses to acute bouts of sprint interval cycling (SIC) and a high-intensity intermittent calisthenics (HIC) protocol consisting of modified "burpees." Eleven (8 men and 3 women) moderately trained, college-aged participants (age = 21.9 ± 2.1, body mass index = 24.8 ± 1.9, V[Combining Dot Above]O2peak = 54.1 ± 5.4 ml·kg·min) completed 4 testing sessions across 9 days with each session separated by 48-72 hours. Using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
54
2
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 28 publications
9
54
2
10
Order By: Relevance
“…2 In this view, even though studies challenge its efficacy in some occasions, 7 the high-intensity training in treadmill 8 bicycle 9 and using the body´s weight 10,11 has been used with the objective to improve levels of physical fitness as well as health, due to its superiority in relation to moderate exercises. [12][13][14] Nonetheless, studies using the HIIT approach and its effects on sweating and hydration rates are still non conclusive in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…2 In this view, even though studies challenge its efficacy in some occasions, 7 the high-intensity training in treadmill 8 bicycle 9 and using the body´s weight 10,11 has been used with the objective to improve levels of physical fitness as well as health, due to its superiority in relation to moderate exercises. [12][13][14] Nonetheless, studies using the HIIT approach and its effects on sweating and hydration rates are still non conclusive in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…As aquatic exercise continues to grow in popularity as an addition, or alternative, to land-based training, it is important for the aquatic instructor to realize that a TS-SWE workout can elicit a substantial metabolic load that is similar to land-based Tabata-style workouts. Furthermore, land-based, relatively brief HIIT results in time-efficient improvements in aerobic power and anaerobic capacity (Astorino, Allen, Roberson, & Jurancich, 2012;Gist et al, 2014;Laurent et al, 2014;Nicolò et al, 2014;Rozenek, Funato, Kubo, Hoshikawa, & Matsuo, 2007;Skelly et al, 2014;Tabata et al, 1997). Given the metabolic and cardiovascular load imposed by the TS-SWE in the current study, one may posit that HIIT performed in shallow water may result in comparable time-efficient metabolic adaptations as land-based HIIT.…”
Section: Discussionmentioning
confidence: 87%
“…During a 20-30 min land-based Tabata-style workout, investigators have found that participants can exercise vigorously or near-maximally to maximally reaching 80-96% of HR max and 74-88% of VO 2 peak (Emberts et al, 2013;Gist et al, 2014;Laurent, Vervaecke, Kutz, & Green, 2014;Skelly et al, 2014). As aquatic exercise continues to grow in popularity as an addition, or alternative, to land-based training, it is important for the aquatic instructor to realize that a TS-SWE workout can elicit a substantial metabolic load that is similar to land-based Tabata-style workouts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations